2013
DOI: 10.1111/febs.12109
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycans and their roles in brain cancer

Abstract: Glioblastoma (GBM), a malignant brain cancer, is characterized by abnormal activation of receptor tyrosine kinase (RTK) signaling pathways and poor prognosis. Extracellular proteoglycans, including heparan sulfate and chondroitin sulfate, play critical roles in the regulation of cell signaling and migration via interactions with extracellular ligands, growth factor receptors, extracellular matrix components, and intracellular enzymes and structural proteins. In cancer, proteoglycans help drive multiple oncogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
162
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(176 citation statements)
references
References 176 publications
(261 reference statements)
7
162
1
1
Order By: Relevance
“…HS and CS thus may be able to act like a protection shield on the surface of cells (cancer and non-cancer), since they protrude out of the cell membrane like a brush [59,60], modulating cell phenotype, growth kinetics, invasiveness and metastatic potential [61][62][63]. Wade et al [64] reported for glioblastoma (GBM) a significant up-regulation of many proteoglycans with differences in the tumor subtypes. Also for melanoma an up-regulation of certain glycosaminoglycans was observed [65].…”
Section: Discussionmentioning
confidence: 99%
“…HS and CS thus may be able to act like a protection shield on the surface of cells (cancer and non-cancer), since they protrude out of the cell membrane like a brush [59,60], modulating cell phenotype, growth kinetics, invasiveness and metastatic potential [61][62][63]. Wade et al [64] reported for glioblastoma (GBM) a significant up-regulation of many proteoglycans with differences in the tumor subtypes. Also for melanoma an up-regulation of certain glycosaminoglycans was observed [65].…”
Section: Discussionmentioning
confidence: 99%
“…Both stabilized brain cancer cell lines and primary cells, obtained from biopsy of CSN tumors, can be used to form spheroids [196]. As frequently happens in the 3D world, neurospheres are more representative of the tumor with respect to the corresponding monolayer cultures.…”
Section: Tumor Brain Spheroids or Neurospheresmentioning
confidence: 99%
“…Структурная и функциональная роль ПГ в возник-новении и развитии злокачественных опухолей голов-ного мозга подробно обсуждается в обзорах [65,66]. Наиболее значимую роль при раке этого типа (глиаль-ные опухоли) играют ХСПГ/ДСПГ и кератансульфат-протеогликаны.…”
Section: протеогликаны в глиальных опухолях головного мозгаunclassified